AN INTEGRATIVE TAXONOMY OF MOLECULAR AND TRADITIONAL APPROACHES FOR IDENTIFICATION OF A STORAGE MITE, ALEUROGLYPHUS OVATUS (ACARI: ASTIGMATA: ACARIDAE) IN MALAYSIA - Che Lah, Ernieenor Faraliana (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
A reliable and rapid taxonomic identification of a mite is the basis for a correct diagnosis of important mite associated allergies as they produce species-specific allergens. A double approach (molecular and morphological) to the taxonomic identification of Aleuroglyphus ovatus was presented. Molecular identification was performed with amplification of the internal transcribed spacer region (ITS2), whilst morphological characters were examined under light microscope. The BLAST results obtained from molecular analysis of A. ovatus was shown to be in concordance with the morphological identification with 97% genetic similarity. Thus, the molecular identification based on the ITS2 region can be applied as a reliable and efficient tool for species identification of Aleuroglyphus and probably any other astigmatid mites. Our findings suggest the need for a broad taxonomic sampling especially from closely related species for an accurate identification of local mites using both DNA sequences and morphology.